A Confucian‐Kantian Response to Environmental Eco‐Centrism on Animal Equality. Issue 3 (25th June 2018) - Palmquist, Stephen R.; Chan, Keith Ka‐Fu
Abstract: Environmental eco‐centrism, the claim that all members of the biosphere are ontologically and axiologically equal, presents a challenge to traditional ethical conceptions of the special status of humanity. Confucian and Kantian ethics approach this topic, and its application to other animals, in different ways: Confucianism employs stories that promote insight into the importance of sincerity and compassion to all animals, including non‐human ones; Kant employs abstract reasoning to argue that non‐human animals deserve respect because we humans share their basic nature. We argue that, taken together, these two approaches preserve what is most important in eco‐centrism, but without sacrificing human dignity in the process.